Copper-alloyed spinel black oxides and tandem-structured solar absorbing layers for high-temperature concentrating solar power systems. (July 2016) - Kim, Tae Kyoung; VanSaders, Bryan; Caldwell, Elizabeth; Shin, Sunmi; Liu, Zhaowei; Jin, Sungho; Chen, Renkun
Highlights: Highly efficient solar absorbing material for high-temperature in-air operation. Tandem CuFeMnO4 and CuCr2 O4 layers with >90% optical to thermal efficiency. Scalable material synthesis (hydrothermal) and coating (spray coating). Stable operation at 750 °C in air for over 500 h and 100 cycles. Abstract: Although renewable solar power plants are rapidly proliferating, high cost and the intermittent availability of solar power are still significant barriers for its penetration into the energy grid system. Concentrating solar power (CSP) offers an attractive alternative due to its integration with cost-effective thermal energy storage systems. To further reduce the cost of CSP, it is imperative to operate the plants at higher temperatures for enhanced efficiency. One of the key components for next-generation high-temperature CSP is the solar absorbing coating materials. In this work, we have developed tandem-structured solar absorbing layers with CuFeMnO4 and CuCr2 O4 black oxide nanoparticles (NPs). These tandem structures exhibited a remarkably high solar-to-thermal conversion efficiency, or figure of merit (FOM), of 0.903, under the condition of 750 °C operating temperature and a solar concentration ratio of 1000. More importantly, the coating showed unprecedented durability, as demonstrated from long-term isothermal annealing at 750 °C in air as well as rapid thermal cycling between room temperature and 750 °C. Our results suggest that the tandem black oxide coating is suitable to meet the stringent demand of next-generation high-temperature CSP systems. The coating materials synthesis, structures, optical as well as thermal properties will be discussed.